Incidence of inpatient cases with mental disorders due to use of cannabinoids in Germany: a nationwide evaluation. (19th January 2022) - Gahr, Maximilian; Ziller, Julia; Keller, Ferdinand; Muche, Rainer; Preuss, Ulrich W; Schönfeldt-Lecuona, Carlos
Abstract: Background: Quantitative (e.g. increasing recreational cannabinoid use) and qualitative (e.g. increasing availability and use of synthetic cannabinoids and cannabis preparations with increased tetrahydrocannabinol content) changes in cannabinoid use may be associated with changes in the prevalence of cannabinoid-related mental and behavioural disorders and, accordingly, changes in the need for medical care. We aimed to investigate if there are changes in the number of inpatient cases (ICs) due to cannabinoid-related disorders in Germany. Methods: Data were obtained from the Federal Statistical Office of Germany (Destatis) and comprised type and number of hospital main diagnoses (according to ICD-10) of all ICs in Germany in the period 2000–18. Linear trend analysis of absolute and relative annual frequencies (AFs) of ICs with diagnoses related to the use of cannabinoids (DRUCs), and, as controls, alcohol-related psychiatric disorders and schizophrenia-spectrum disorders was performed. Results: Absolute AFs of ICs with DRUCs increased statistically significantly ( P <0.0001, trend analysis) in Germany between 2000 and 2018 and corresponding relative AFs increased considerably (4.8-fold increase when comparing 2000 and 2018). Specifically, absolute AFs of ICs with cannabinoid intoxications ( P <0.0001), harmful use ( P =0.0005), dependence syndrome ( P < 0.0001), withdrawal state ( P <0.0001), psychotic disorders ( P < 0.0001) and residual and late-onset psychotic disorder ( P <0.0001) statistically significantly increased. Absolute AFs of schizophrenia-spectrum disorders slightly, but statistically significantly decreased ( P =0.008), and alcohol dependence did not statistically significantly change ( P =0.844). Conclusions: Our evaluation demonstrates increasing numbers of ICs with mental and behavioural disorders due to use of cannabinoids in Germany and emphasizes the need for adequate prevention of such disorders.